Signal transduction, dimerization, and therapeutic targeting of Orexin and receptor systems - Zhang, Shengnan; Wang, Peixiang; Ji, Bingyuan; Shao, Yuming; Hou, Sen; Chen, Jing; Wang, Chunmei (Frontiers in Pharmacology, 2025)
Orexin receptors (OXRs), including OX1R (HCRTR1) and OX2R (HCRTR2), are G protein-coupled receptors (GPCRs) that are activated by endogenous orexin peptides (OXA and OXB) and have potential pleiotropic effects in nervous system, which makes them highly valuable therapeutic targets. Emerging evidence indicates that OXRs exhibit a significant propensity to form homodimers and heterodimers with various GPCRs, generating biased signaling that may offer a platform for precision pharmacology and enable the design of pathway-specific drugs with fewer off-target effects. Current and emerging OXR antagonists demonstrate efficacy in sleep disorders, metabolic dysregulation, and psychiatric conditions. Furthermore, transmembrane (TM) peptides targeting specific dimer interfaces represent a novel therapeutic strategy. This review synthesizes current understanding of orexin receptor systems, focusing on the structural composition, signal transduction pathways, dimerization properties, and antagonist compounds of OXRs. We present a comprehensive overview of the current state of research, investigate the molecular pathological mechanisms associated with neurological disorders, and evaluate potential therapeutic targets for pharmaceutical development.